2018
DOI: 10.1021/acsnano.8b02153
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Ratchet in Cylindrical Nanowires

Abstract: The unidirectional motion of information carriers such as domain walls in magnetic nanostrips is a key feature for many future spintronic applications based on shift registers. This magnetic ratchet effect has so far been achieved in a limited number of complex nanomagnetic structures, for example, by lithographically engineered pinning sites. Here we report on a simple remagnetization ratchet originated in the asymmetric potential from the designed increasing lengths of magnetostatically coupled ferromagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 53 publications
1
72
0
1
Order By: Relevance
“…This control of magnetization processes by changing the composition is particularly interesting since it has been recently shown that changes in composition can lead to full control of magnetization processes in NWs . Even more, the introduction of local changes in the composition in NWs, in which magnetization processes are fully controlled by magnetostatic interactions, can introduce topologically protected magnetic structures, very interesting from both the theoretical and application point of view …”
mentioning
confidence: 99%
“…This control of magnetization processes by changing the composition is particularly interesting since it has been recently shown that changes in composition can lead to full control of magnetization processes in NWs . Even more, the introduction of local changes in the composition in NWs, in which magnetization processes are fully controlled by magnetostatic interactions, can introduce topologically protected magnetic structures, very interesting from both the theoretical and application point of view …”
mentioning
confidence: 99%
“…This is valid for either two types of magnetic materials (Ivanov et al 2016a; Fig. 13c), or one magnetic and the other one nonmagnetic (Grutter et al 2017, Bran et al 2018. In case the segments display a transverse shape or magnetocristalline anisotropy, each may display a type of domain on its own, e.g.…”
Section: Modulated and 3d Structuresmentioning
confidence: 97%
“…The impact of an Oersted field has also been considered to assist nucleation, as the curling mode has the same symmetry as the Oersted field (Otalora et al 2015). Nucleation as a function of (short) wire length has also been investigated (Sergelius et al 2017), with application to the realization of a ratchet in multisegmented wires with an axial gradient of segment length (Bran et al 2018).…”
Section: Nucleation Of Domain Wallsmentioning
confidence: 99%
See 2 more Smart Citations